Dietary flavone chrysin (5, 7-dihydroxyflavone ChR) functionalized highly-stable metal nanoformulations for improved anticancer applications. Issue 109 (21st October 2015) - Sathishkumar, G.; Bharti, Rashmi; Jha, Pradeep K.; Selvakumar, M.; Dey, Goutam; Jha, Rakhi; Jeyaraj, M.; Mandal, Mahitosh; Sivaramakrishnan, S.
Abstract : A new approach to formulate biofunctionalized metallic silver (ChR–AgNPs) and gold (ChR–AuNPs) nanoparticles using ChR as a direct bioreductant and capping agent as a combinational drug-nano platform for breast cancer therapy. Abstract : Nanomaterials of noble metals with unique size, shape and composition receives much attention owing to their versatile functionality in personalized cancer nanomedicine. Chrysin (ChR), a natural anticancer bioflavonoid, emerged as a potential drug therapy for almost all types of cancer, however it has poor solubility and bioavailability. Herein, we report a new approach to formulate biofunctionalized metallic silver (ChR–AgNPs) and gold (ChR–AuNPs) nanoparticles using ChR as a direct bioreductant and capping agent. Size and dispersity of nanoparticles (NPs) were controlled through fixing different reaction conditions such as the temperature, pH, concentration of metal ion, stoichiometric proportion of the reaction mixture and incubation time based on their optical properties and SPR effect in UV-visible spectroscopy. The role of hydroxyl and carbonyl groups in functionalizing the metal ions with ChR was confirmed with Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) analysis. It was also substantiated that the oxygen group from ChR donates electrons to metal ion and results in complexation; ionic Ag + and Au 3+ were reduced to Ag 0 and Au 0 nano-forms. The physiochemical state of obtained NPs was characterized through different exclusive instrumentation, which shows the presence of highly-stable, spherical, crystalline ChR–AgNPs and ChR–AuNPs with an average size of 14 ± 6 nm and 6 ± 2 nm respectively. In vitro anticancer results revealed that the formulated metallic NPs exhibit enhanced cytotoxicity over ChR in the treatment of two different breast carcinoma cell lines (MDA-MB-231 and MDA-MB-468). Furthermore, it was evident that the NPs cause cell death via the induction of apoptosis. A hemolysis assay with human erythrocytes demonstrates good blood biocompatibility of the NPs. Thus, the ChR functionalized metal NPs can be potentially employed as a combinational drug-nano platform for breast cancer therapy.